Mild Cognitive Impairment and Depressive Symptoms in Elderly Patients with Diabetes: Prevalence, Risk Factors, and Comorbidity - Malgorzata Gorska-Ciebiada; Malgorzata Saryusz-Wolska; Maciej Ciebiada; Jerzy Loba (Journal of Diabetes Research)
The aim of the study was to estimate the prevalence of mild cognitive impairment (MCI), depressive syndrome cases, and its comorbidity, and to identify predictors of these conditions. Methods. 276 diabetics elders were screened for MCI and depressive symptoms. Detailed information of history of diabetes, and data of BMI, HbA1c, and blood lipids were collected. Results. The prevalence of MCI was 31.5%, depressive syndrome was 29.7%, and MCI with coexisting depressive mood was 9.1%. The logistic regression analysis revealed that variables which increased the likelihood of having been diagnosed with MCI were: higher HbA1c level, previous CVD, hypertension, retinopathy, increased number of comorbidities, and less years of formal education. Significant predictors of having a depressive mood included female gender, single marital status, current and past smoking status, lack of physical activity, higher BMI and total cholesterol level, increased number of comorbidities, history of hypoglycemia, and insulin treatment. Factors associated with both MCI and depressive syndrome were female gender, single marital status, past smoking status, retinopathy, previous CVD or stroke, increased number of comorbidities, and insulin treatment. Conclusions. Depressive symptoms, MCI, and its comorbidity are common in elderly subjects with type 2 diabetes. Systematic screening could result in the identification of high-risk patients.